The fourth Bent-toed Gecko of the genus Cyrtodactylus (Squamata: Gekkonidae) from Java, Indonesia - Riyanto, Awal; Grismer, L. Lee; Wood, Perry L. Jr. (Zootaxa, 2015)
Cyrtodactylus petani sp. nov. is a new species of Bent-toed Gecko from Java, Indonesia that had been masquerading under the name C. fumosus (Müller, 1895). The new species is differentiated from C. fumosus and all its Sundaland congeners by having the following combination of morphological characters: a maximum SVL of 57.2 mm; nine or ten supralabials; seven or eight infralabials; strongly tuberculate body and limbs; 20–25 paravertebral tubercles; 30–35 ventral scales; enlarged precloacal scales; enlarged femoral scales; 17–18 subdigital lamellae on the fourth toe; 31–35 continuous precloacal and femoral pores in males, pores absent in females; no precloacal groove; no enlarged median subcaudals; tubercles on anterior portion of tail; no reticulated pattern on top of head; a blotched dorsal pattern; and no paired, dark, semi-lunar shaped blotches on the nape.